Insecticide ear tags numerically improve grazing cattle performance - S.E. Hill; Brandon E. Oleen; William R. Hollenbeck; Christopher I. Vahl; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2013)
Stocker cattle grazing pastures during the summer months face challenges due to horn flies, which can result in reduced weight gains and less efficient use of forages. One strategy for controlling horn flies is insecticide-impregnated ear tags. The use of pesticide ear tags may be an effective management practice to improve overall productivity during a grazing season. The objective of this study was to evaluate the efficacy of insecticide ear tags as a means of improving growth of stocker calves grazing native pastures in the Flint Hills region of Kansas.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Swine; Insecticide ear tags; Stocker cattle; Gain; Cattle performance